ChemInform Abstract: Synthesis of Normorphans Through an Efficient Intramolecular Carbamoylation of Ketones. Issue 51 (December 2015) - Diaba, Faiza; Montiel, Juan A.; Serban, Georgeta; Bonjoch, Josep
Abstract: A novel intramolecular carbamoylation of amidocyclohexanones (I) is developed which proceeds via enamine formation followed by cyclization and concomitant cleavage of the trichloromethyl group.